Lessons Learned from Two Decades of Anticancer Drugs. (October 2017) - Liu, Zhichao; Delavan, Brian; Roberts, Ruth; Tong, Weida
Abstract : Tremendous efforts have been made to elucidate the basis of cancer biology with the aim of promoting anticancer drug development. Especially over the past 20 years, anticancer drug development has developed from conventional cytotoxic agents to target-based and immune-related therapies. Consequently, more than 200 anticancer drugs are available on the market. However, anticancer drug development still suffers high attrition during the later phases of clinical development and is considered to be a difficult and risky therapeutic category within the drug development arena. The disappointing performance of investigational anticancer candidates implies that there are some shortcomings in the translation of preclinical in vitro and in vivo models to humans, and that heterogeneity in the patient population presents a significant challenge. Here, we summarize both successful and failed experiences in anticancer development during the past 20 years and help identify why the current paradigm may be suboptimal. We also offer potential strategies for improvement. Trends: As emerging techniques continue to impact cancer genomics, precision oncology may be implemented in anticancer drug development if firmly grounded. Novel mechanisms and novel concepts of cancer pathogenesis, such as cancer stem cells and cancer-derived induced pluripotent stem cells, provide new opportunities to model the cancer genome and may generate new avenues for anticancer drug development. Drug combinations naturally fit for multiple cancer pathologies and tend to be the major anticancer drug development focus. Gene editing is being tested in humans. In the near future, it may be applied to expand knowledge of cancer genomics and facilitate novel models in anticancer development.